The Question of Value: A Review of Michael Clayton - Pei-Suin Ng (Opticon1826, 2008)
In civil law, value is invariably reduced to lucre. The suffering of trauma and injury is measured by restitution; a lawsuit is appraised by the award of damages. Defending a corporation against clear liability, in turn, is a yielding of million-dollar billings to shore up the profits of the law firm and guarantee the bonuses of its partners. The currency of value is a prominent theme in Tony Gilroy’s Michael Clayton, a cinematic web of legal drama, sinister double-dealing and corporate wrongdoing.